Single-Stage Air Filtration of Particles and Gaseous Contaminants in Buildings: A Literature Study. Issue 3 (November 2020) - Orlando, Roberta; Fojan, Peter; Mo, Jinhan; Bergsøe, Niels C.; Afshari, Alireza
Abstract: A variety of air filtration technologies are commercially available for reducing particles and gaseous contaminants that may enter buildings from outside. According to the World Health Organization (WHO), there is an increasing range of adverse health effects linked to air pollution, at even-lower concentration of pollutants. This article presents a short literature overview of air filtration technologies, which focus on assessing their ability in removing both particles and gaseous compounds. The aim is to provide information about current research development of air filtration technologies as well as their advantages, limitations and performance in terms of removal efficiency, pressure drop and formation of by-products. Mechanical filters and electrostatic filters are efficiently used for the removal of particles. Photocatalytic oxidant and adsorbent air filters are commonly used for gas removal. These last two types of filters are not feasible for particles removal. Air filtration using electrospun nanofiber filters have been studied, however, the performance of such filters for the removal of particles and gaseous contaminants at the same time has to be further investigated.